Bilateral sudden sensorineural hearing loss: a rare case report - Hosea, Libason (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Sudden sensorineural hearing loss refers to the unexplained rapid onset of hearing loss occurring in a person who was apparently well. The exact cause of this nature of hearing loss is unknown in most cases, although it is linked to viral infections, vascular compromise or coagulation disorders in the blood, metabolic conditions such as diabetes mellitus, autoimmune conditions of the inner ear, endolymphatic hydrops such as in Meniere’s disease, or traumatic injury to the inner ear. A case of a 20-year-old male who was apparently healthy before presenting with the sudden onset of bilateral hearing loss, accompanied by tinnitus and dizziness was presented. There was no headache, loss of consciousness, or visual disturbance, and the patient had no history of head trauma. Otoscopy, anterior rhinoscopy, and neurological examination were apparently normal. The diagnosis of sudden sensorineural hearing loss was made, and the patient’s pure tone audiometry results showed profound sensorineural hearing loss on the right side, and moderate sensorineural hearing loss on the left. The patient was treated with methylprednisolone and acyclovir. We have presented a rare case of bilateral sudden sensorineural hearing loss in a young adult male who had no risk factors. The cause of sudden sensorineural hearing loss in this patient was thought to be idiopathic.